Desafios da inclusão na sala de aula comum: prática de ensino colaborativo em uma escola da rede municipal de Santa Maria - Zambeli, Lisania Barbosa (2023)
This dissertation is part of the LP2 research line, Gestão Pedagógica e Contextos Educativos, of the Programa de Pós-Graduação em Políticas Públicas e Gestão Educacional, Mestrado Profissional, at the Universidade Federal de Santa Maria (UFSM). The study arises from the questions that permeate inclusive education, specifically the challenges of inclusion in the ordinary classroom, based on practices that involve the pedagogical work of ordinary and special education teachers, based on collaborative teaching. The overall aim of the research is to develop, describe, and analyze collaborative teaching practices in a 1st grade elementary school class at a school in the Santa Maria Municipal Education Network, and it is divided into specific objectives that aim to: analyze the contributions of collaborative teaching to students' learning, pedagogical practices and teachers' training processes; identify the challenges and possibilities of implementing collaborative teaching in the school context; and produce an Ebook of collaborative practices with the activities experienced in the collaborative teaching experience. The theoretical foundations underpinning this work are based on the theoretical contributions of Philippe Meirieu (1998, 2002, 2005, 2006), on pedagogical practices and educational relationships, and authors such as Capellini (2004, 2007, 2019), Zerbato (2019), Mendes (2007, 2011, 2018), Almeida (2011), Toyoda (2011), Vilaronga (2018), Bridi, Castro and Menezes (2016), on the conceptualization and characterization of Collaborative Teaching. The methodology used has a qualitative approach, with collaborative-critical action research as the research method. The locus of the research was a municipal school in Santa Maria. The participants in the research were: the ordinary school teacher, the special education teacher, and the students in the class. Data was collected by analyzing the pedagogical practices carried out by the teachers, based on collaborative teaching, the teachers' field diaries, and a semi-structured interview with the special education teacher. The research included four analytical axes that permeate collaborative teaching: 1) collaborative teaching: effects on pedagogical practices; 2) students' learning experiences from the perspective of collaborative teaching; 3) the teachers' training process through the practice of collaborative teaching; and 4) the challenges and possibilities of collaborative teaching in the school context. By analyzing the findings through pedagogical practices based on collaborative teaching, it was possible to perceive the importance of this work between common education and special education teachers, as it offers benefits in the schooling of all students, as well as the qualification of teachers' pedagogical practices. It is hoped that this research will instigate reflection on the possibilities of collaborative teaching in schools. As a result, the product of the research is an Ebook in digital format, called "Inspiration for collaborative teaching" and its purpose will be to share the work developed and instigate, based on pedagogical practices, teachers to think about the possibility of materializing collaborative teaching within their classrooms.